2012
DOI: 10.1007/s10549-012-2273-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of health insurance, hospital factors and physician volume on receipt of immediate post-mastectomy reconstruction in women with invasive and non-invasive breast cancer

Abstract: For women with breast cancer who undergo mastectomy, immediate breast reconstruction (IR) offers a cosmetic and psychological advantage. We evaluated the association between demographic, hospital, surgeon and insurance factors and receipt of IR. We conducted a retrospective hospital-based analysis with the Perspective database. Women who underwent a mastectomy for invasive breast cancer (IBC) and ductal carcinoma in situ (DCIS) from 2000 to 2010 were included. Logistic regression analysis was used to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
66
1
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(79 citation statements)
references
References 44 publications
8
66
1
4
Order By: Relevance
“…We also found no indication that marital status influenced the choice of reconstruction. This result is in line with the findings in a substantial number of other studies [2,5,6,26,38,41], although a higher rate of reconstruction among married women has been reported [30,42].…”
Section: Discussionsupporting
confidence: 91%
“…We also found no indication that marital status influenced the choice of reconstruction. This result is in line with the findings in a substantial number of other studies [2,5,6,26,38,41], although a higher rate of reconstruction among married women has been reported [30,42].…”
Section: Discussionsupporting
confidence: 91%
“…We have found previously that racial/ethnic disparities that favor Whites exist for a substantial number of treatments and interventions. [35][36][37][38] This was found in addition to the fact that lower SES patients were also less likely to undergo colonoscopy at 1 year; thus, both factors were associated with receipt of this procedure independently. Our studies have also found that being married versus being single is usually associated with increased compliance with the appropriate guidelines and receipt of the appropriate treatment or intervention, as in this study.…”
Section: Discussionmentioning
confidence: 84%
“…Age less than 50 years was a constant and best predictor of having breast reconstruction. 20,21,24,25,[31][32][33][34] Some physicians fear offering breast reconstruction to older women, due to their coexisting morbidities and perceived increase in complications. However, breast reconstruction is a safe and feasible option in older patients.…”
Section: Ratesmentioning
confidence: 99%
“…20 Other studies have shown that women with commercial insurance had a threefoldhigher likelihood of undergoing immediate reconstruction compared to those without insurance. 34 A Southern California study found that patients with private insurance were ten times more likely to undergo reconstruction than patients with Medi-Cal insurance. 24 In contrast, patients who are considered financially indigent and who receive their care at a university-based public hospital are more likely to have breast reconstruction.…”
Section: Ratesmentioning
confidence: 99%